Jack and Jill, and other nursery rhymes (Rand McNally Chicago, 1958)
This collection features classic nursery rhymes, including the adventures of Jack and Jill as they go up the hill to fetch a pail of water. Each rhyme is accompanied by charming illustrations, making it a delightful read that introduces children to rhythm and storytelling.